Penerapan Terapi Seni dan Suportif untuk Menurunkan Depresi Berat pada Perempuan Korban Kekerasan Seksual - Harisma Fakhrun Nisa'; Dessy Pranungsari (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
This intervention used art and supportive therapy to relieve depressive symptoms in a woman victim of sexual violence. The art therapy utilized a creative process to help the participant explore herself through drawing as a medium emphasizing freedom in communication, so it was expected that it would help her cope with problems. The supportive therapy aimed to provide encouragement and efficacy for the participant so she could develop insight. The participant in this report was one female victim of sexual violence who had symptoms of depression. The measuring instrument used to determine the participant’s level of depression was the Beck Depression Invetory-II (BDI-II). Then, the effectiveness of the intervention was evaluated using a qualitative descriptive analysis highlighting some changes from before to after the intervention. The results showed that the participant’s depressive symptoms decreased from the pre-intervention measurement.